Fabrication of material patterns by grid-assisted deposition - Massi, Massimiliano; Cavallini, M.; Stagni, S.; Palazzi, F.; Biscarini, F. (Elsevier Science, 2003)
We developed a simple patterning approach where a grid with micrometer rule is used in order to control the deposition of a solute. Ordered patterns were obtained, over large areas, in a few seconds. The patterning process we propose here is fast and low cost. It can also be applied to diverse soluble molecular and supramolecular species. We also investigated what parameters have to be changed in order to have total control on the final tridimensional architecture of the material.